FRASE NOMINA DALAM ARTIKEL BEYOND FILM: EXPLORING THE CONTENT OF MOVIE OLEH JOHN SCACCO - Usman, Ramona (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research is entitled Noun Phrases in Journal Article Beyond Film: Exploring the Content of Movie by John Scacco. The objectives research is to identify and classify the kinds of noun phrases and to analyze the internal functions of noun phrases. This research used descriptive method. The writer collected the data of noun phrases from article Beyond Film: Exploring the Content of Movie by John Scacco, which consists of 4 pages. After collecting the data, the writer analyzed the internal functions of noun phrases by using the theory of Aarts and Aarts (1982). The results of this research first, there are 90 noun phrases found in journal article Beyond Film: Exploring the Content of Movie by John Scacco. Noun phrases are distinguished in three functions: head, determiner and modifier. The noun phrases that are most widely used is head (65), determiner is 22 include pre determiner (12), central determiner (5) and post determiner (3). There are 9 modifiers include pre modifier (3) and post modifier (6) but discontinuous modifiers are not found in this research. Secondly the result show that the internal function of noun phrases is divided into three: pre modifier, post modifier and discontinuous modifier. The pre modifier found in the journal article: pre modifier realized by adjective phrase (1), noun phrase (1), and a classifying genitive (2) while post modifier can be filled with prepositional phrase (1), finite clause (2) and infinitive clause (1). Adjective phrase (0) and adverb phrase (0) are not found in this research. Â  KEYWORDS: Internal function, Noun Phrase, Article Beyond Film: Exploring the Content of Movie.